Free Lunch Policy Analysis: A Comparative Study of Law and Economics in Japan, China, and India - nabilarahmawatirama; Leli Joko Suryono; Katherine Mazzer (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study analyzes the implementation of free lunch policies in three Asian countries: Japan, China, and India. The free lunch policy is necessary to improve child health, support educational participation, and reduce the economic burden on families. Through a comparative case study approach, this research evaluates the implementation, successes, and challenges of the policy in three countries. In Japan, the institutionalized free lunch program significantly reduced family expenditure and increased parental productivity, contributing to social welfare. China implemented the policy to reduce economic disparities in rural and urban areas, showing improvements in children's nutritional status and the financial well-being of low-income families. The research method used is by analyzing policy documents and reviewing the literature. The results show that the free lunch policy not only directly benefits children's health and Education but also significantly positively impacts the economy of families and communities. This finding confirms that the free lunch policy can improve the community's economic welfare. The study concludes the successful implementation of the free lunch policy in each country. The study concludes that the successful implementation of the free lunch policy largely depends on the amendment of the free lunch policy in each country, community involvement, and adequate supervision.